2019
DOI: 10.15666/aeer/1704_89698983
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis on the Relationship Between Green Economy and Inflation in China

Abstract: Targeting the 21 port provinces of China, this paper constructs a panel vector autoregressive (PVAR) model to explore the dynamic relationship between China's green economy and inflation, and to verify whether China's green economy has a negative effect on inflation. Both the global Malmquist-Luenberger (GML) index and the Malmquist-Luenberger (ML) index, which represent the production efficiency under pollution, were adopted to measure China's green economy. It is assumed that the green economy and inflation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…At the same time, increasing the city’s investment in green innovation will cause large-scale agglomeration of production factors, subject to the constraints of the external environment. Accordingly, urban price levels will continue to rise and even cause inflation; such “green governance” inflation stress is also considered as an undesirable output [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, increasing the city’s investment in green innovation will cause large-scale agglomeration of production factors, subject to the constraints of the external environment. Accordingly, urban price levels will continue to rise and even cause inflation; such “green governance” inflation stress is also considered as an undesirable output [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Human input R&D personnel full-time equivalent Chen [14] Resources input Per unit GDP energy consumption Liu [17] Capital inputs Fiscal expenditure on science and technology Zhang [15]; Clausen [34] Internal R&D expenditures Sueyoshi [16] Output indicators Technological benefit Number of invention patents granted Liu [17]; Cuerva [35] Economic benefit Revenue from new product sales Liu [9]; Cuerva [35] Environmental benefit Comprehensive environmental treatment rate Du [18]; Song [36] Undesirable outputs Number of unauthorized patents Feng [19]; Carayannis [37] "Green governance" inflation pressure LYU [38] "Transformative" unemployment rate Reiff [39] technology aspect. The input of green innovation forces the urban industry to transform from labor-intensive to technology-intensive and capital-intensive industries.…”
Section: Input Indicatorsmentioning
confidence: 99%
“…analyzed the relationships between carbon dioxide emissions per capita in kilotons, food production index (FPI), renewable energy consumption share of renewable energy in the total energy consumed in kilotons (REC), and inflation rate as measured by the consumer price index (INF) which reflects the annual percentage in the cost to the average consumer of acquiring a basket of goods and services, for the period 1995-2014 Alola et al (2019). found that REC and INF decrease emissions in the long run but food production increases emissions in the long run for panel countries which are 16 coastline Mediterranean countries including Turkey Lyu (2019). analyzed the relationship between the green economy and INF in China for 21 port provinces by panel vector autoregressive model (PVAR) for the period 2006-2015.…”
mentioning
confidence: 99%